Response of some Citrus species to frost damage at the central area of Santa Fe, Argentina - Micheloud, Norma Guadalupe; Castro, Damián César; Favaro, María Alejandra; Buyatti, Marcela Alejandra; Pilatti, Rubén Andrés; Gariglio, Norberto Francisco (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The aim of this work was to quantify frost damage and the reproductive and vegetative behaviour of some Citrus species after intense frost events registered between June 7th and 8th 2012. After the frost events, trees showed severe fruit drop, partial or total defoliation and eventually, tree death. Growth response during the following growing season showed that percentage of sprouting (y) was inversely related to defoliation (x) caused by frost (y=146. 32-0.92x). Flowering intensity was reduced in the majority of the citrus varieties tested, with a relative increase of vegetative and leafy shoots. Fruit set was increased (69-92%) in relation with years without frost occurrence with the exception of tangerines. Fruit yield of each variety was related with its mean flowering intensity at the central area of Santa Fe. Those cultivars which normally reach high flowering intensities (>250 flowers per 100 nodes) showed higher fruit yield, up to 67% compared to non-frost years. In the other hand, cultivars which normally reach lower flowering intensities showed low fruit yields (<26.3- 84.5%) in comparison with non-frost years.